Serotonin receptor 2B signaling with interstitial cell activation and leaflet remodeling in degenerative mitral regurgitation. (February 2018) - Driesbaugh, Kathryn H.; Branchetti, Emanuela; Grau, Juan B.; Keeney, Samuel J.; Glass, Kimberly; Oyama, Mark A.; Rioux, Nancy; Ayoub, Salma; Sacks, Michael S.; Quackenbush, John; Levy, Robert J.; Ferrari, Giovanni
Abstract: Aims: Mitral valve interstitial cells (MVIC) play an important role in the pathogenesis of degenerative mitral regurgitation (MR) due to mitral valve prolapse (MVP). Numerous clinical studies have observed serotonin (5HT) dysregulation in cardiac valvulopathies; however, the impact of 5HT-mediated signaling on MVIC activation and leaflet remodeling in MVP have been investigated to a limited extent. Here we test the hypothesis that 5HT receptors (5HTRs) signaling contributes to MVP pathophysiology. Methods and results: Diseased human MV leaflets were obtained during cardiac surgery for MVP; normal MV leaflets were obtained from heart transplants. MV RNA was used for microarray analysis of MVP patients versus control, highlighting genes that indicate the involvement of 5HTR pathways and extracellular matrix remodeling in MVP. Human MV leaflets were also studied in vitro and ex vivo with biomechanical testing to assess remodeling in the presence of a 5HTR2B antagonist (LY272015). MVP leaflets from Cavalier King Charles Spaniels were used as a naturally acquired in vivo model of MVP. These canine MVP leaflets (N = 5/group) showed 5HTR2B upregulation. This study also utilized CB57.1ML/6 mice in order to determine the effect of Angiotensin II infusion on MV remodeling. Histological analysis showed that MV thickening due to chronic Angiotensin II remodeling is mitigated by a 5HTR2B antagonist (LY272015) but not by 5HTR2A inhibitors. Conclusion: In humans, MVP is associated with an upregulation in 5HTR2B expression and increased 5HT receptor signaling in the leaflets. Antagonism of 5HTR2B mitigates MVIC activation in vitro and MV remodeling in vivo . These observations support the view that 5HTR signaling is involved not only in previously reported 5HT-related valvulopathies, but it is also involved in the pathological remodeling of MVP. Highlights: Microarray and Network Reconstruction analysis in MVP patients and controls reveals a role for the 5HT signaling pathway in myxomatous mitral valve pathology. 5HTR2B is upregulated in human MVP leaflets when compared to control as well as in a canine model of myxomatous mitral regurgitation. A 5HTR2B antagonist (LY 272015) reduces MVICs activation under biomechanical stimulation ex vivo . LY 272015 prevents Angiotensin II-mediated heart valve thickening in vivo . We reported for the first time a mechanistic connection between serotonin receptor signaling and one of the most common heart valve diseases, MVP, a disorder affecting millions of patients.